History of the Yogyakarta Monarchy: From the Islamic Kingdom to Being Imprisoned in the Indonesian Democratic System - Catur Nugroho; Wisma Nugraha Christianto; Sugeng Bayu Wahyono (Historia Madania: Jurnal Ilmu Sejarah, 2021)
Collaboration between democracy and monarchy occurs in government systems in several countries. What happened in Yogyakarta was a monarchy system that originated from the Islamic Mataram kingdom, which was later recognized as a political institution that held executive power in the democratic system of the Indonesian state. The King of Yogyakarta acts as the holder of executive power (Governor) in the Special Region of Yogyakarta. With the method of literature review and theoretical elaboration, this paper seeks to explore how the history of monarchy in Yogyakarta can collaborate and operate in the democratic system in Indonesia. This paper also looks at and analyzes how the development of the Yogyakarta Palace and Sultan Hamengku Buwono, who played the role of King and then at the same time held the position of Governor of the Special Region of Yogyakarta. From the analysis, it is found that Yogyakarta is an Islamic kingdom that later joined the Indonesian state as one of the provinces with a special status. The current position of the Special Region of Yogyakarta is a "prison" for Sultan Hamengkubuwono. As a King, the Sultan is always supervised by the regional people's representative council in the implementation of regional governance. The King of Yogyakarta, who appears to have dual powers as a King as well as a Governor, is, in fact, nothing more than prisoners imprisoned within the palace walls under the strict supervision of the representative council and the central government